KERUGIAN MASYARAKAT AKIBAT PEMBATASAN LALU LINTAS DENGAN SISTEM GANJIL GENAP - Mujiono, Wisnu Dwihutomo Putro; Ratnawati, Elfrida (Ensiklopedia of Journal, 2024)
People in Jakarta have suffered losses due to the enactment of Traffic Restrictions with an Odd-Even System, where the enactment of these regulations has not been able to solve the problem of traffic congestion that occurs in Jakarta. As a result of traffic congestion in Jakarta, the community experiences losses in terms of expensive travel costs due to more fuel used, vehicle maintenance costs due to longer engine usage and unstable vehicle movements, medical costs due to high levels of gas emissions exposed from the impact of congestion, reduced income earned by workers due to sanctions or fines due to late arrival at the office. The DKI Jakarta government in dealing with congestion that occurs in Jakarta imposes traffic restrictions with an even odd vehicle number system. This has caused a new polemic for the community, with this regulation the level of congestion in Jakarta has not decreased significantly, and the community has a social impact where the community feels that their right to be able to use road facilities is limited without any compensation given such as a reduction in vehicle tax costs. This paper aims to understand the impact of even-odd rules that are enforced in Jakarta. with a normative juridical approach method, where this legal research emphasizes the examination of legal documents and library materials related to the subject matter. This research uses secondary data obtained from primary and secondary legal materials. Based on the results of this study, it can be concluded that the odd-even legal policy has a detrimental impact on society and also affects the social situation in society, especially in DKI Jakarta, these rules need to be review.Keywords: Traffic Restrictions, Odd-even, Congestion